Logo
3. Binomische Formel Aufgaben mit Lösungen

Aufgaben

Wende auf die Aufgaben die dritte binomische Formel an.

Aufgabe 1:
(2x + 2y) · (2x - 2y)

Aufgabe 2:
(3x + 8y) · (3x - 8y)

Aufgabe 3:
(2x + 3y) · (2x - 3y)

Aufgabe 4:
(3x + 5y) · (3x - 5y)

Aufgabe 5:
(6x + 4y) · (6x - 4y)

Aufgabe 6:
(10x + 2y) · (10x - 2y)

Aufgabe 7:
(1x + 9y) · (1x - 9y)

Aufgabe 8:
(4x + 6y) · (4x - 6y)

Aufgabe 9:
(6x + 2y) · (6x - 2y)

Aufgabe 10:
(2x + 4y) · (2x - 4y)

Aufgabe 11:
(5x + 4y) · (5x - 4y)

Aufgabe 12:
(5x + 8y) · (5x - 8y)


Anzeige

Lösungen

Aufgabe 1:
(2x + 2y) · (2x - 2y) = 4x2 - 4y2

a = 2xa2 = (2x)2 = 4x2
b = 2yb2 = (2y)2 = 4y2

Aufgabe 2:
(3x + 8y) · (3x - 8y) = 9x2 - 64y2

a = 3xa2 = (3x)2 = 9x2
b = 8yb2 = (8y)2 = 64y2

Aufgabe 3:
(2x + 3y) · (2x - 3y) = 4x2 - 9y2

a = 2xa2 = (2x)2 = 4x2
b = 3yb2 = (3y)2 = 9y2

Aufgabe 4:
(3x + 5y) · (3x - 5y) = 9x2 - 25y2

a = 3xa2 = (3x)2 = 9x2
b = 5yb2 = (5y)2 = 25y2

Aufgabe 5:
(6x + 4y) · (6x - 4y) = 36x2 - 16y2

a = 6xa2 = (6x)2 = 36x2
b = 4yb2 = (4y)2 = 16y2

Aufgabe 6:
(10x + 2y) · (10x - 2y) = 100x2 - 4y2

a = 10xa2 = (10x)2 = 100x2
b = 2yb2 = (2y)2 = 4y2

Aufgabe 7:
(1x + 9y) · (1x - 9y) = 1x2 - 81y2

a = 1xa2 = (1x)2 = 1x2
b = 9yb2 = (9y)2 = 81y2

Aufgabe 8:
(4x + 6y) · (4x - 6y) = 16x2 - 36y2

a = 4xa2 = (4x)2 = 16x2
b = 6yb2 = (6y)2 = 36y2

Aufgabe 9:
(6x + 2y) · (6x - 2y) = 36x2 - 4y2

a = 6xa2 = (6x)2 = 36x2
b = 2yb2 = (2y)2 = 4y2

Aufgabe 10:
(2x + 4y) · (2x - 4y) = 4x2 - 16y2

a = 2xa2 = (2x)2 = 4x2
b = 4yb2 = (4y)2 = 16y2

Aufgabe 11:
(5x + 4y) · (5x - 4y) = 25x2 - 16y2

a = 5xa2 = (5x)2 = 25x2
b = 4yb2 = (4y)2 = 16y2

Aufgabe 12:
(5x + 8y) · (5x - 8y) = 25x2 - 64y2

a = 5xa2 = (5x)2 = 25x2
b = 8yb2 = (8y)2 = 64y2


Anzeige